The place of the Cabinet of ministers of Ukraine in the system of public administration entities - Dneprov, Oleksii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article, based on the current legal framework, modern scientific developments and developments, defines the place of the Cabinet of Ministers of Ukraine as the highest executive body in the system of public administration. It is determined that the substantive essence of the category "public administration" should be considered in a broad and narrow sense. In a narrow sense, public administration is closely linked to the executive branch and is seen as the professional activity of civil servants and social workers, non-governmental organizations, institutions and organizations with budget funding and sponsorship to ensure vital activities of the country at the level of state, regional and local government and carry out the study, development and implementation of public policy. Public administration in a broad sense is related to the functioning of all branches of government: legislative, executive and judicial. It is noted that in the framework of administrative law, as well as in the study of administrative activities of the Cabinet of Ministers of Ukraine, it is advisable to use a narrow approach to this category. The system of subjects of public administration is clarified. It is determined that the system of the main subjects of public administration can be represented as follows: executive bodies, which consist of three levels - higher, central, local; local governments; subjects of delegated authority. It is determined that the Cabinet of Ministers of Ukraine has a leading place in the process of carrying out executive and administrative activities as a kind of public administration. It is noted that the powers of the Cabinet of Ministers of Ukraine play an important role in this context, the implementation of which is a direct manifestation of the implementation of this subject of public administration. The author finds that the Cabinet of Ministers is endowed with powers in the following areas: 1) in the field of economy, finance, labor relations, employment, labor migration, pay and labor protection; 2) in the areas of social policy, health care, education, science, culture, sports, tourism, environmental protection and emergency response; 3) in the areas of legal policy, legality, ensuring human and civil rights and freedoms et al.